2009
DOI: 10.4028/www.scientific.net/kem.413-414.175
|View full text |Cite
|
Sign up to set email alerts
|

Gearbox Fault Diagnosis Based on Vibration Signals Measured Remotely

Abstract: In many cases, it is impractical to measure the vibrations directly at or close to their source. It is a common practice to measure the vibration at a location far from the source for condition monitoring purposes. The vibration measured in this way inevitably has high distortions from the vibrations due to the effect of the attenuation of signal paths and the interference from other sources. The suppression of the distortions is a key issue for the remote measurements based condition monitoring. In this paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 3 publications
0
2
0
2
Order By: Relevance
“…Castellani in 2020 [58] studied the solution to measure vibrations at the tower instead of at the gearbox in a wind turbine and achieved positive outcomes in the bearing diagnostics without impacting the wind turbine operation. Al-Arbi in 2009 [57] treated the distortions suppression for the remote measurements issue and it emerged that the results of the different signal processing techniques were highly influenced by the signal attenuation and interference. Among the tested SP methods, time synchronous average (TSA) proved to be less sensitive to the problem.…”
Section: Multiple Sourcesmentioning
confidence: 99%
“…Castellani in 2020 [58] studied the solution to measure vibrations at the tower instead of at the gearbox in a wind turbine and achieved positive outcomes in the bearing diagnostics without impacting the wind turbine operation. Al-Arbi in 2009 [57] treated the distortions suppression for the remote measurements issue and it emerged that the results of the different signal processing techniques were highly influenced by the signal attenuation and interference. Among the tested SP methods, time synchronous average (TSA) proved to be less sensitive to the problem.…”
Section: Multiple Sourcesmentioning
confidence: 99%
“…齿轮传动是各种机器设备中应用最广泛 的动力和运动传递装置,其动力性能对整个 机器有重要影响,所以对齿轮故障进行准确 监测具有重要意义 [1] 。当前,基于振动的监 测是这类机器的主流监测手段。但是这种方 法故障报警率高、设备成本也较高且传感器 安装不便。为了克服振动监测的这些弊端, 很多研究者将电机电流信号分析作为机械 故障诊断的方法,这种方法不仅成本较低而 且可以实现远距离监测,更为有利的是信号 中除了包含正常运转的信息外,还包含了运 行工况信息,因此可以建立精确可靠的变负 荷模型进行状态监测 [2] 。然而,故障信号通 常非常小,并被大量的 50Hz 的供应电源信 号和随机噪声信号所掩盖,所以需要应用有 效的信号处理方法来提取小信号。2000 年 Benbozide 应用电机电信号监测了电机自身 的故障 [3] 。2007 年 Nagi 等人沿伸了电机电 流信号分析的应用,运用传统双谱分析对电 机电流信号进行了分析并证明了电流信号 可用来检测多级变速箱的齿轮不同破损情 况 [4] 。2011 年郑州大学李凌均提出了矢双谱 分析方法,通过采集安装在齿轮箱上的传感 器采集的数据,应用双谱分析方法提取信号 特征信息,实现了对齿轮箱的智能故障诊断 [5] 。 [7] : ) 2 cos( 2 …”
Section: .前言unclassified
“…It has been shown that wavelet reconstruction improves fault classification when used in fault diagnostics. Al-Arbi et al [9] The attenuation and interference have a significant negative impact on the gear transmission signals, according to the study of data from many signals processing approaches. However, the time synchronous average (TSA) efficiently detects local gear system failures.…”
Section: Introductionmentioning
confidence: 99%